The study of genetic factors that determine the awned glume trait in bread wheat - O. B. Dobrovolskaya; A. E. Dresvyannikova; E. D. Badaeva; K. I. Popova; M. Trávníčková; P. Martinek (Вавиловский журнал генетики и селекции)
Awns are bristle‐like structures, typically extending from the tip end of the lemmas in the florets of cereal species, including such economically important crops as wheat (Triticum aestivum L., T. durum Desf.), barley (Hordeum vulgare L.), rice (Oryza sativa L.), and rye (Secale cereale L.). The presence of long awns adhered at tip end of glumes is a characteristic feature of “Persian wheat” T. carthlicum Nevski spike. Glume outgrowth of T. carthlicum Nevski spike passes into a long awn, equal in length to the lemma awn. Awned glumes can be formed in T. aestivum and T. aethiopicum wheats, however, such forms are rare. Features of the awned glume development and the genetic determinants of this trait have been little studied. In this paper, we described the features of the development and inheritance of the tetra-awness (awned glume) trait of the bread wheat T. aestivum line CD 1167-8, using classical genetic analysis, molecular genetic mapping, and scanning electron microscopy. It was shown that the trait is inherited as a recessive monogenic. The gene for the awned glume trait of CD 1167-8 was mapped in the long arm of chromosome 5A, using the Illumina Infinium 15K Wheat Array (TraitGenetics GmbH), containing 15,000 SNPs associated with wheat genes. Results of allelism test and molecular-genetic mapping suggest that the gene for awned glumes in bread wheat is a recessive allele of the B1 awn suppressor. This new allele was designated the b1.ag (b1. awned glume). Analysis of the CD 1167-8 inflorescence development, using scanning electron microscopy, showed that awns had grown from the top of the lemmas and glumes simultaneously, and no differences in patterns of their development were found.